Effect of Glucose Concentration on the Production of Proteolytic Extract by Different Strains of Aspergillus under Solid-State Fermentation - Londoño-Hernández, Liliana; García Gómez, María de Jesús; Huerta-Ochoa, Sergio; Polanía-Rivera, Anna María; Aguilar, Cristóbal Noé; Prado-Barragán, Lilia Arely (Fermentation, 2024)
Proteases are important enzymes due to their wide range of applications in several industries, such as food, beverages, pharmaceuticals, detergents, among others. Aspergillus is one of the most widely used fungal genera for enzyme production by solid-state fermentation (SSF). Availability of the carbon source is a key factor for protease production. In addition, the selection of the solid support is of great importance, as it must provide suitable airflow through the packed bed and allow nutrient diffusion within the fermentable mass. Six Aspergillus strains and two inert supports (Agrolite (AL) and Polyurethane (PUF)) were evaluated for protease production from fish flour (FF) at different glucose concentrations (0, 5, 10, and 15%) by SSF. The FF/PUF mixture at a 70/30 (w/w) ratio, with 75.39% moisture content and a critical moisture point of 0.11 g H₂O/g, exhibited a texture that facilitated heat and mass transfer and provided sufficient moisture to ensure the availability of free water required for microbial growth during the fermentation process. Aspergillus oryzae 2095 produced higher amounts of neutral and alkaline proteases when 5% glucose was added to the growth medium. Kinetic studies revealed that protease production is partially growth-associated. The extracts obtained can be applied in different industries, particularly for the production of high-value fish by-product hydrolysates.
Keywords: Producción de proteasa; Concentración de glucosa; Soporte inerte